Expression of genes kdsA and kdsB involved in 3-deoxy-D-manno-octulosonic acid metabolism and biosynthesis of enterobacterial lipopolysaccharide is growth phase regulated primarily at the transcriptional level in Escherichia coli K-12. - Strohmaier, H (1995)
We have cloned and sequenced a cluster of six open reading frames containing gene kdsA from Escherichia coli K-12. The gene encodes 3-deoxy-D-manno-octulosonate 8-phosphate synthetase (KDO-8-phosphate synthetase), which catalyzes formation of 3-deoxy-D-manno-octulosonic acid (KDO), an essential component of enterobacterial lipopolysaccharide. We have also identified two other genes, hemA and prfA, at the beginning of the cluster. Deletion analysis shows that kdsA, the terminal gene of this putative operon, is transcribed from its own promoter located within the cluster rather than from two promoters preceding this group of six open reading frames. Northern (RNA) blot analysis as well as lacZ operon fusion experiments reveal that the expression of gene kdsA occurs maximally in the early log phase and falls to a low level in the late log and stationary phases. Hence, this gene is subjected to growth phase-dependent regulation at the transcriptional level. Similarly, we show that expression of gene kdsB, which codes for the CTP:CMP-3-deoxy-D-manno-octulosonate cytidyltransferase (CMP-KDO-synthetase), is also growth regulated. This enzyme catalyzes the activation of KDO via formation of CMP-KDO, which is necessary for the incorporation of KDO into lipid A. We have identified the promoter of gene kdsB, whose expression is growth regulated in the same way as that of kdsA. Despite the fact that transcription of genes kdsA and kdsB is shut off as cells enter stationary phase, KDO-8-phosphate synthetase as well as CMP-KDO-synthetase activities are still present at various levels during stationary-phase growth of an E. coli K-12 culture.